Political psychology in the Philippines an update. [article]. - Montiel, Cristina Jayme .
Filipino political psychology studies the psychological processes and behaviors of Filipinos involved in power situations. Due to its context-sensitive nature, the field of political psychology evolves in different ways, depending on the historical and political context within which it is embedded. The historical embeddedness of political psychology is thematic in this review. Philippine political psychology has been enriched by the colorful politico-historical changes in the country. Philippine research from the early 60's until the 1980's shows the close relationship between psychological processes and political situations, in studies on: kinship and political power, political socialization, social conflict, democratic transition, and public opinion surveys As the new democracy stabilized new fields of Philippine political psychology developed such as; Filipino electoral behaviors, political influence of the church, political personalities, peace psychology, ideological groups, women in politics, corruption and empowerment. The future of the Filipino political psychology can be strengthened by teaching more college courses related to this field, building a strong research-based body of knowledge, and mainstreaming the discipline so it becomes less marginalized in the dominant discourses of political science and psychology in the Philippines.